Management of iron‐deficiency anemia following acute gastrointestinal hemorrhage: A narrative analysis and review. Issue 1 (7th November 2022) - Lanas, Angel; Andrews, Jane M; Lau, James; Toruner, Murat; Bromley, Susan E; Gralnek, Ian M
Abstract: Many patients experiencing acute gastrointestinal bleeding (GIB) require iron supplementation to treat subsequent iron deficiency (ID) or iron‐deficiency anemia (IDA). Guidelines regarding management of these patients are lacking. We aimed to identify areas of unmet need in patients with ID/IDA following acute GIB in terms of patient management and physician guidance. We formed an international working group of gastroenterologists to conduct a narrative review based on PubMed and EMBASE database searches (from January 2000 to February 2021), integrated with observations from our own clinical experience. Published data on this subject are limited and disparate, and those relating to post‐discharge outcomes, such as persistent anemia and re‐hospitalization, are particularly lacking. Often, there is no post‐discharge follow‐up of these patients by a gastroenterologist. Acute GIB‐related ID/IDA, however, is a prevalent condition both at the time of hospital admission and at hospital discharge and is likely underdiagnosed and undertreated. Despite limited data, there appears to be notable variation in the prescribing of intravenous (IV)/oral iron regimens. There is also some evidence suggesting that, compared with oral iron, IV iron may restore iron levels faster following acute GIB, have a better tolerability profile, and be more beneficial in terms of quality of life. Gaps in patient care exist in the management of acute GIB‐related ID/IDA, yet further data from large population‐based studies are needed to confirm this. We advocate the formulation of evidence‐based guidance on the use of iron therapies in these patients, aiding a more standardized best‐practice approach to patient care.